The role of an abnormal prostate-specific antigen level and an abnormal digital rectal examination in the diagnosis of prostate cancer: A cross-sectional study in Qatar() - Al Rumaihi, Khalid (Arab J Urol, 2013)
OBJECTIVE: To investigate the role of an abnormal prostate-specific antigen (PSA) level and abnormal findings on a digital rectal examination (DRE) in the detection of prostate cancer in men in Qatar. PATIENTS AND METHODS: Between June 2008 and September 2012, 651 patients had a transrectal ultrasonography-guided biopsy of the prostate (TRUSBP) at our centre. The indications for a biopsy were a high PSA level (>4 ng/mL), or an abnormal DRE result. Patients were assessed by a thorough history, clinical examination and routine laboratory investigations. Data, including age, DRE findings, TRUS findings, total PSA level, prostate volume and the pathology results, were evaluated. RESULTS: The mean (SD) age of the 651 patients was 64.1 (7.4) years. Prostate cancer was detected in 181 men (27.8%), benign prostatic hyperplasia in 275 (42.2%) and prostatitis in 236 (36.4%). The sensitivity and specificity for detecting prostate cancer were 93.9% and 8.5% for an abnormal PSA level (>4 ng/mL), 46.1% and 84.7% for abnormal DRE findings, and 95% and 30.2% for the two combined. Using a receiver operating characteristics curve, a PSA threshold of 7.9 ng/mL had a sensitivity of 56.6% and specificity of 52.8%. When a PSA threshold of 7.9 ng/mL was used in combination with abnormal DRE findings, the overall accuracy was 76.9%. CONCLUSION: The PSA threshold level of 7.9 ng/mL, determined by this analysis, has a higher likelihood of detecting prostate cancer in men in Qatar. However, it failed to detect cancer in substantially many men with statistically significant disease.